Konsep Dasar Evaluasi Pembelajaran - Laila Laila; Alawiyah Nabila; Eka Widyanti (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The learning process of students can be assessed through evaluation methods. The purpose of this evaluation is to assess learning outcomes as well as to evaluate the learning process. The concept of learning evaluation involves the control, assurance, and establishment of learning quality for all components at various levels and pathways of education, which is the responsibility of educational management. Assessment is the process of using various methods and tools to collect information about specific learning outcomes. Measurement, in English, refers to an action taken to adjust something. The basic way of measuring is by comparing something to a certain standard. Educators provide a series of tasks or questions to students to gauge their understanding and reach an agreement between students and teachers regarding the taught material, in line with current learning objectives, commonly referred to as tests. Therefore, it can be concluded from the table that tests are a benchmark for success in delivering education through educational assessment.